Crazy Representations of Natural Numbers From 20001 to 40000 - Inder J. Taneja (Zenodo, 2021)
This paper brings natural numbers from 20001 to 40000 written in \textbf{ascending} and \textbf{descending} orders of 1 to 9. The numbers are obtained by using basic operations, and \textbf{factorial}. For previous results see author's works [work1, work2,   work3].  For more details and comments see author's site link
Keywords: Crazy Representations, Recreating Numbers, Natural Numbers, Increasing Order, Decreasing Order